2013
DOI: 10.1155/2013/904370
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin Suppresses Burn-Induced Lipid Peroxidation and Reduces Fluid Requirements in a Swine Model

Abstract: Objective. Lipid peroxidation plays a critical role in burn-induced plasma leakage, and ulinastatin has been reported to reduce lipid peroxidation in various models. This study aims to examine whether ulinastatin reduces fluid requirements through inhibition of lipid peroxidation in a swine burn model. Methods. Forty miniature swine were subjected to 40% TBSA burns and were randomly allocated to the following four groups: immediate lactated Ringer's resuscitation (ILR), immediate LR containing ulinastatin (ILR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Studies have confirmed that UTI can inhibit the formation of ROS induced by oxidants, through preventing the leakage of JC-1 from mitochondria to the cytoplasm, increasing the level of intracellular ATP to protect mitochondrial function, reducing the release of cytochrome c from mitochondria to the cytoplasm, inhibiting the activation of cysteine protease-3, and preventing the destruction of AJs ( 172), finally increasing the permeability of vascular endothelium mediated by antioxidants. Luo et al found that UTI infusion significantly reduced the plasma and tissue concentrations of thiobarbituric acid reactive substances (TBARS) in post-burn miniature pig models, suggesting that UTI can decrease vascular permeability possibly by inhibiting burn-induced lipid peroxidation (173). In recent years, some studies have been conducted on the protective effect of UTI on cell apoptosis, but the detailed mechanism of UTI's ability to inhibit the formation of reactive oxygen mediators induced by oxidants and its relationship with apoptosis remain to be clarified by future research.…”
Section: Thrombinmentioning
confidence: 99%
“…Studies have confirmed that UTI can inhibit the formation of ROS induced by oxidants, through preventing the leakage of JC-1 from mitochondria to the cytoplasm, increasing the level of intracellular ATP to protect mitochondrial function, reducing the release of cytochrome c from mitochondria to the cytoplasm, inhibiting the activation of cysteine protease-3, and preventing the destruction of AJs ( 172), finally increasing the permeability of vascular endothelium mediated by antioxidants. Luo et al found that UTI infusion significantly reduced the plasma and tissue concentrations of thiobarbituric acid reactive substances (TBARS) in post-burn miniature pig models, suggesting that UTI can decrease vascular permeability possibly by inhibiting burn-induced lipid peroxidation (173). In recent years, some studies have been conducted on the protective effect of UTI on cell apoptosis, but the detailed mechanism of UTI's ability to inhibit the formation of reactive oxygen mediators induced by oxidants and its relationship with apoptosis remain to be clarified by future research.…”
Section: Thrombinmentioning
confidence: 99%
“…23 Lipid peroxidation, leading to generation of reactive oxygen species, plays a critical role in burn-induced plasma leakage by contributing to the increased microvascular permeability, edema formation, and tissue damage after burn injury. 12 , 23 Septicemia/sepsis, shock, and multiorgan failure are recognized as the most common causes of death in burn injury patients. 6 , 19 , 22 , 24–26 Burn shock can develop rapidly after major burn injury, and current treatment mainly includes early adequate fluid resuscitation with the aim of maintaining sufficient tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al, in 2013, 12 reported attenuation of increase in vascular permeability and net fluid accumulation along with reduced fluid requirements in a swine model with 40% TBSA burn injury, with the use of ulinastatin. Ulinastatin has also been studied in other animal models of burn injury and has demonstrated significant decrease in the levels of inflammatory mediators, oxygen-free radicals, and protective effect on multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…highlighted the utility for large animal models of burn-induced SIRS in studying the effects of the urinary trypsin inhibitor, ulinistatin [165]. Another study examined mobilization of mononuclear cells after a 30%TBSA scald burn [166].…”
Section: Burn Pathophysiologymentioning
confidence: 99%